Diverse wildfire impacts on river flows across the globe - Manolis Grillakis; Apostolos Voulgarakis (Communications Earth & Environment)
Abstract Forest fires can significantly impact the hydrological regime of river basins, affecting short-term flood propensity and long-term water resource availability until vegetation is reestablished. While basin-level studies have extensively investigated these impacts, regional and global-scale assessments remain limited. Here we use a comprehensive global dataset of river discharge observations to systematically assess the hydrological response to wildfires for a range of hydrologically homogenous world regions and biomes. Our analysis reveals contrasting hydrological impacts by region, with high-latitude discharge ratios declining by 7.5% and 16% in the first and second year after wildfire, respectively, while Northern mid-latitude regions showing a marginal 3.3% median increase in discharge ratio the first-year post-fire. Sub-tropical and equatorial regions display negative and positive effects, respectively. We further discuss how potential ecological and hydroclimatic factors, along with human river and watershed management, shape these diverse hydrological responses per hydroclimatic region.